The ability of Waist -Triglyceride Index to Identify Metabolic Syndrome among Adults from Jaffna - Paramanathan, T.; Kumanan, T.; Arasaratnam, V. (Faculty of Medicine, University of Colombo, 2023)
Metabolic syndrome (MetS) criteria include Waist Circumference (WC) and Triglycerides (TG). A combination of TG with WC may be useful to detect MetS instead of considering either TG or WC alone. This study was carried out to evaluate the ability of Waist -Triglyceride Index (WTI) to identify MetS, to compare with TG and WC, and to determine WTI cut-off values to predict MetS in adults from the Jaffna
Keywords: Metabolic syndrome; Waist-triglyceride index; Triglycerides; Waist circumference; Discriminative ability